A new feature selection method based on association rules for diagnosis of erythemato-squamous diseases - Karabatak, Murat; Ince, M. Cevdet (Pergamon-Elsevier Science Ltd, 2009)
In this paper, a new feature selection method based on Association Rules (AR) and Neural Network (NN) is presented for the diagnosis of erythemato-squamous diseases. AR is used for reducing the dimension of erythemato-squamous diseases dataset and NN is used for efficient classification. The proposed AR+NN system performance is compared with that of other feature selection algorithms+NN. The dimension of input feature space is reduced from thirty four to twenty four by using AR. In test stage, 3-fold cross validation method is applied to the erythemato-squamous diseases dataset to evaluate the proposed system performances. The correct classification rate of proposed system is 98.61%. This research demonstrated that the AR can be used for reducing the dimension of feature space and proposed AR+NN model can be used to obtain fast automatic diagnostic systems for other diseases. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Association rules; Neural network; Erythemato-squamous; Feature selection